Comunidades de leveduras associadas com a fermentação espontânea durante a produção artesanal da cachaça de Alambique em Minas Gerais - Carla Pataro (2000)
The yeast communities associated with the fermentation of cachaça were studied in 19 distilleries in the State of Minas Gerais. Was performed to monitor the formation of starter and fermentation of wine, both during the fermentation cycle of 24 hours and in different seasons (beginning, middle and end of production of cachaça). A succession of yeast species was observed during fermentation with Saccharomyces cerevisiae dominating the process. Yeast species or transient contaminants as Candida guilliermondii, C. stellata, membranifaciens Pichia, Kluyveromyces lactis and Kloeckera japonica var drosophilarum were found in varying numbers, probably due to the daily addition of fresh sugar cane juice. It was observed that changes in fermented, such as increased acidity and alcohol content, along with high concentrations of sugar maintained by daily addition of sugar cane in yeast can act in the selection of yeast species prevalent. Tests conducted in the laboratory, to evaluate the ability of yeast strains to produce micocinas ("killer") showed their presence in both starter vat, and in fermented, suggesting their role as responsible for the disappearance of some species contaminants. However, no strain "killer" dominated the fermentation of sugarcane juice. More than 60% of the strains were neutral to the toxins produced by isolates "killer". In starter, 56.5% of the isolates were sensitive to toxins, while sensitive strains comprised approximately 40% of the isolates in the vats young (early production of cachaça) and 32.5% in the fermentation old ( end of production). Most isolates of S. cerevisiae were able to grow on medium with high osmotic concentration between 25 and 40%, and ethanol concentrations between 8-12%. Were also considered a growth between 37 and 400 C. The ability to produce invertase and trehalose accumulate in normal growth conditions (stationary phase) was variable among the isolates studied, with strains of S. cerevisiae showed the higher the values, with the exception of one strain of C. sake which was capable of producing more than 200 mmol / reducing sugar / mg cells / min to 300 C. The results showed that strains of S. cerevisiae tested able to accumulate trehalose under conditions of heat stress and ethanol showed higher survival in these conditions. PFGE and PCR analysis of predominant lineages of S. cerevisiae isolated from fermented showed high level of genetic polymorphism in the three distilleries sampled. The high molecular variability of strains of S. cerevisiae was observed in strains isolated from the same fermentation vat and different ages. Our results showed that there is a succession of strains of S. cerevisiae genetically different times during the fermentation process for producing the cachaça